Immediate dental implants placed into infected sites present a higher risk of failure than immediate dental implants placed into non-infected sites: Systematic review and meta-analysis - De Oliveira-Neto, Olavo-Barbosa; Lemos, Cleidiel-Aparecido-Araújo [UNESP]; Barbosa, Fabiano-Timbó; De Sousa-Rodrigues, Célio-Fernando; Camello De Lima, Fernando-José (Medicina Oral, S.L., 2019)
Background: Alveolar infection is known as a risk factor for implant failure. Current meta-analysis on the theme could not prove statistically that immediate dental implants placed into infected sites have a higher risk of failure than immediate dental implants placed into non-infected sites. The purpose of this meta-analysis was to determine the effectiveness of immediate dental implants placed into infected versus non-infected sites. Material and Methods: Seven databases were sought by two reviewers. Randomized or non-randomized clinical trials that compared the placement of dental implants into infected versus non-infected sites were eligible for the study. Exclusion criteria were: papers in which the survival rate was not the primary outcome; papers without a control group; studies with less than one year of follow-up; studies whose patients did not receive antibiotic therapy; studies with medically compromised patients; duplicated papers. Risk of bias assessment was performed with the Cochrane Collaboration tool. Results: Of the 3.253 initial hits, 8 studies were included in both qualitative and quantitative synthesis (kappa= 0.90; very good agreement). Forest plot for implant failure showed that immediate implants placed into infected sites presented a statistically significant risk of failure that is almost 3 times higher than when placed into non-infected sites (risk ratio= 2.99; 95% confidence interval: 1.04, 8.56; p= 0.04; 935 implants; i2= 0%). Peri-implant outcomes showed no statistical difference. Conclusions: Immediate dental implants placed into infected sites presented a statistically significant higher risk of failure than immediate dental implants placed into non-infected sites. Peri-implant outcomes were not statistically affected in this intervention.
Keywords: Dental implants; Immediate placement; Infection; Systematic review; Tooth socket